2000
DOI: 10.1128/jb.182.13.3673-3680.2000
|View full text |Cite
|
Sign up to set email alerts
|

ComP, a Pilin-Like Protein Essential for Natural Competence in Acinetobacter sp. Strain BD413: Regulation, Modification, and Cellular Localization

Abstract: We recently identified a pilin-like competence factor, ComP, which is essential for natural transformation of the gram-negative soil bacterium Acinetobacter sp. strain BD413. Here we demonstrate that transcription and synthesis of the pilin-like competence factor ComP are maximal in the late stationary growth phase, whereas competence is induced immediately after inoculation of a stationary-phase culture into fresh medium. Western blot analyses revealed three forms of ComP, one with an apparent molecular mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 45 publications
2
48
0
1
Order By: Relevance
“…To this end, naturally competent isolates 07-095 and 07-102 and their pilT and comEC mutant derivatives were stab inoculated into motility agarose and the bacteria were collected from the surface and the interphase. In accordance with published work on Acinetobacter pili (17,(42)(43)(44), thin (ϳ 4 nm wide) and thick (ϳ 7 nm wide) pili could be observed. In both parental strains, the thick pili were only rarely found in surface-grown bacteria (approximately 1 pilus per 25 to 50 cells with a typical length of up to 2 m) and even more sporadic in the interphase-derived preparations ( Table 2).…”
Section: Dosupporting
confidence: 75%
“…To this end, naturally competent isolates 07-095 and 07-102 and their pilT and comEC mutant derivatives were stab inoculated into motility agarose and the bacteria were collected from the surface and the interphase. In accordance with published work on Acinetobacter pili (17,(42)(43)(44), thin (ϳ 4 nm wide) and thick (ϳ 7 nm wide) pili could be observed. In both parental strains, the thick pili were only rarely found in surface-grown bacteria (approximately 1 pilus per 25 to 50 cells with a typical length of up to 2 m) and even more sporadic in the interphase-derived preparations ( Table 2).…”
Section: Dosupporting
confidence: 75%
“…While no systematic attempt has yet been made to characterize the 54 regulon in Acinetobacter spp., 54 has been shown to be required for the utilization of phenol and benzyl alkanoates as metabolic substrates in A. baylyi (73,133). The expression of ComP, a pilin-like protein essential for transformational competence in A. baylyi ADP1, is present at the highest levels during late stationary phase and also is likely to be regulated by 54 (210). It was recently found that genes under the control of the 54 -regulated Pu promoter from Pseudomonas putida could be expressed exogenously in A. baylyi ADP1 (111).…”
Section: Alternative Sigma Factors and Their Regulationmentioning
confidence: 99%
“…Proteins involved in uptake of DNA via natural transformation have been studied in several gram-negative bacteria, such as Neisseria gonorrhoeae (15,51,57), Acinetobacter sp. strain BD413 (14,41), Haemophilus influenzae (9), Pseudomonas stutzeri (16,17), Helicobacter pylori (1,21,48), and Synechocystis sp. strain PCC6803 (58), and some gram-positive bacteria, such as Bacillus subtilis and Streptococcus pneumoniae (6,12,39).…”
mentioning
confidence: 99%